PROBLEMS OF MODIFICATION STEEL CASTINGS BY NANOPARTICLES - V. Kovalevskij; A. Zhuk; A. Kovalevskaja; S. Grigor’ev; K. Zhuk (Литьë и металлургия)
It is suggested to use steel shot with the structure of tempered martensite for smelt modifying in the capacity of carriermodifier. It was applied barrier nickel layer and then wolfram nano-coating (over 200 nm) along with protective cobalt layer, which prevents interreaction of oxygen with wolfram surface. Introduction of the modifier creates subcooling zone. When it interreacts with smelt the process of active mixing of the modifier with the smelt takes place. Subsequent crystallization carries involving large number of crystallization centers, which leads to reduction in the structure graininess and velocity and plasticity increase by 2–3 times.